Kinetic plasma dynamics in a radial model of a Hall thruster with a curved magnetic field. (1st November 2022) - Marín-Cebrián, Alberto; Domínguez-Vázquez, Adrián; Fajardo, Pablo; Ahedo, Eduardo
Abstract: A 1D particle-in-cell model of a Hall thruster discharge is used to analyze the effect of a curved magnetic topology in the radial plasma response and the plasma fluxes to dielectric walls. The kinetic solution shows a significant replenishment of the velocity distribution function tail and temperature isotropization for both negative (i.e. anode pointing) and positive curvatures. The new radial magnetic force is electron confining or expanding for, respectively, negative and positive curvatures, and this modifies significantly the electric and pressure radial forces. As a consequence, the plasma density near the wall and the degree of radial ion defocusing are affected: they are highly reduced for negative curvatures, the case of higher interest. For positive curvatures, the kinetic solution shows that the radial ion flow becomes supersonic within the plasma bulk, away from the Debye sheaths. An ancillary quasineutral fluid model is presented to explain this feature and other aspects of the kinetic solution. Some kinetic studies on additional phenomena complete the work.